Surface-induced dissociation of protein complexes on a cyclic ion mobility spectrometer. Issue 22 (11th October 2021) - Snyder, Dalton T.; Jones, Benjamin J.; Lin, Yu-Fu; Cooper-Shepherd, Dale A.; Hewitt, Darren; Wildgoose, Jason; Brown, Jeffery M.; Langridge, James I.; Wysocki, Vicki H.
Abstract : Characterization of protein assemblies and amyloid aggregates by CIU, CID, SIU, and SID on a cyclic ion mobility spectrometer. Abstract : We describe the implementation of a simple three-electrode surface-induced dissociation (SID) cell on a cyclic ion mobility spectrometer (cIMS) and demonstrate the utility of multipass mobility separations for resolving multiple conformations of protein complexes generated during collision-induced and surface-induced unfolding (CIU & SIU) experiments. In addition to CIU and SIU, SID of protein complexes is readily accomplished within the native instrument software and with no additional external power supplies by entering a single SID collision energy, a simplification in user experience compared to prior implementations. A set of cyclic homomeric protein complexes and a heterohexamer with known CID and SID behavior were analyzed to investigate mass and mobility resolution improvements, the latter of which improved by 20–50% (median: 33%) compared to a linear travelling wave device. Multiple passes of intact complexes, or their SID fragments, increased the mobility resolution by an average of 15% per pass, with the racetrack effect being observed after ∼3 or 4 passes, depending on the drift time spread of the analytes. Even with modest improvements to apparent mobility resolving power, multipass experiments were particularly useful for separating conformations produced from CIU and SIU experiments. We illustrate several examples where either (1) multipass experiments revealed multiple overlapping conformations previously unobserved or obscured due to limited mobility resolution, or (2) CIU or SIU conformations that appeared 'native' in a single pass experiment were actually slightly compacted or expanded, with the change only being measurable through multipass experiments. The work conducted here, the first utilization of multipass cyclic ion mobility for CIU, SIU, and SID of protein assemblies and a demonstration of a wholly integrated SIU/SID workflow, paves the way for widespread adoption of SID technology for native mass spectrometry and also improves our understanding of gas-phase protein complex CIU and SIU conformationomes.